2015
DOI: 10.1111/ijd.12999
|View full text |Cite
|
Sign up to set email alerts
|

An open‐label, single‐arm trial of the safety and efficacy of a novel preparation of glutathione as a skin‐lightening agent in Filipino women

Abstract: The authors conclude that the lozenge containing glutathione was safe and effective in lightening the skin of Filipino women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 15 publications
1
64
0
Order By: Relevance
“…A total of 1,176 articles was found but four articles were included (Figure ) . Two studies were conducted in Thailand, while the other two were conducted in the Philippines . Three studies were RCTs with placebo control and the other was a single‐arm study .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 1,176 articles was found but four articles were included (Figure ) . Two studies were conducted in Thailand, while the other two were conducted in the Philippines . Three studies were RCTs with placebo control and the other was a single‐arm study .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated the effect of glutathione on skin color compared to placebo . The remaining study reported such effect of oral glutathione with no comparison . All studies used skin melanin index measured by Mexameter ® as the outcome.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations